2016
DOI: 10.1002/2016jd024935
|View full text |Cite
|
Sign up to set email alerts
|

HF radar observations of a quasi‐biennial oscillation in midlatitude mesospheric winds

Abstract: The equatorial quasi‐biennial oscillation (QBO) is known to be an important source of interannual variability in the middle‐ and high‐latitude stratosphere. The influence of the QBO on the stratospheric polar vortex in particular has been extensively studied. However, the impact of the QBO on the winds of the midlatitude mesosphere is much less clear. We have applied 13 years (2002–2014) of data from the Saskatoon Super Dual Auroral Radar Network HF radar to show that there is a strong QBO signature in the mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 85 publications
(115 reference statements)
3
9
0
Order By: Relevance
“…The 11-year solar cycle effect is captured, in which the atomic oxygen density is 17 % smaller in 2008/2009 (minimum of solar cycles 23/24) than in 2002 (near solar maximum conditions of solar cycle 23), due to different radiative forcing conditions during the solar cycles. This agrees with model investigations and experimental results, which are normally in a range of around 10 % to 30 % (Schmidt et al, 2006;Marsh et al, 2007;Kaufmann et al, 2014;Zhu et al, 2015). A significant semiannual oscillation is observed, reaching a maximum in equinox seasons, which is in agreement with the analysis above for Fig.…”
Section: Spatial and Temporal Analysissupporting
confidence: 92%
“…The 11-year solar cycle effect is captured, in which the atomic oxygen density is 17 % smaller in 2008/2009 (minimum of solar cycles 23/24) than in 2002 (near solar maximum conditions of solar cycle 23), due to different radiative forcing conditions during the solar cycles. This agrees with model investigations and experimental results, which are normally in a range of around 10 % to 30 % (Schmidt et al, 2006;Marsh et al, 2007;Kaufmann et al, 2014;Zhu et al, 2015). A significant semiannual oscillation is observed, reaching a maximum in equinox seasons, which is in agreement with the analysis above for Fig.…”
Section: Spatial and Temporal Analysissupporting
confidence: 92%
“…The coupling between the lower atmosphere and the ionosphere‐thermosphere (IT) system remains one of the biggest challenges in understanding and observing space weather. Numerous studies have been conducted over the past few decades to understand the dynamical and compositional changes in the IT densities and temperature because of the lower atmosphere (e.g., Hagan & Forbes, 2002; Immel et al, 2006; Malhotra et al, 2016; Shimazaki, 1967, 1968; X. Zhang et al, 2010b, 2010a, etc.). The vertical coupling via gravity waves, planetary waves, and atmospheric tides plays a crucial role in the momentum, energetics, and composition of the IT system (Lindzen, 1981; Qian et al, 2009; Siskind et al, 2014; Yamazaki & Richmond, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The coupling between the lower atmosphere and the ionosphere-thermosphere (IT) system remains one of the biggest challenges in understanding and observing space weather. Numerous studies have been conducted over the past few decades to understand the dynamical and compositional changes in the IT densities and temperature because of the lower atmosphere (e.g., Hagan & Forbes, 2002;Immel et al, 2006;Malhotra et al, 2016;Shimazaki, 1967Shimazaki, , 1968X. Zhang et al, 2010bX.…”
Section: Introductionmentioning
confidence: 99%
“…However, further investigations using Medium-Frequency (MF) and meteor radars observations over the equatorial and low latitude reported relatively much smaller MQBO amplitudes ranging from 3.5 to 6 m/s (refer to Table 1 of deWit et al., 2013). Even though the MQBO is an equatorial phenomenon, evidences for its existence in the mid-and high-latitude upper mesosphere have been reported (Ford et al, 2009;Malhotra et al, 2016;Namboothiri et al, 1993). Malhotra et al (2016) reported that the QBO amplitudes from earlier studies using meteor and MF radar observations over mid-latitude are in the range of 1 and 7 ms −1 .…”
mentioning
confidence: 99%